Chemical composition and antibacterial activity of essential oils against pathogens often related to cattle endometritis - Renan Braga Paiano; Jeannine Bonilla; Ricardo Luiz Moro de Sousa; Andrea Micke Moreno; Pietro Sampaio Baruselli (Journal of Infection in Developing Countries)
Introduction: Endometritis is a condition marked by inflammation of the endometrium that affects dairy cows from 21 days after parturition, causing damage to herd fertility and economic losses on farms. The use of active compounds obtained from plant sources has gained importance as disease treatment agents in farm animals due to the high resistance rates currently observed against traditional antibiotics commonly used. The study was carried out to examine the chemical composition and to investigate the antibacterial activity of rosemary, cinnamon, cloves, eucalyptus, lemon, oregano and thyme essential oils against the reference strain of Escherichia coli (ATCC 25922), Fusobacterium necrophorum (ATCC 25286), Trueperella pyogenes (ATCC 19411) and Staphylococcus aureus (ATCC 29213), considered as typical bacteria causing endometritis.